Development and Acceptability of Locally Made Fish-Based, Ready-to-Use Products for the Prevention and Treatment of Malnutrition in Cambodia. Issue 3 (September 2018) - Sigh, Sanne; Roos, Nanna; Sok, Daream; Borg, Bindi; Chamnan, Chhoun; Laillou, Arnaud; Dijkhuizen, Marjoleine A.; Wieringa, Frank T.
Background: Cambodia has a high prevalence of moderate acute malnutrition and severe acute malnutrition (SAM). The SAM treatment requires ready-to-use therapeutic foods (RUTFs), whereas ready-to-use supplementary foods (RUSFs) are used for prevention of acute malnutrition. Three locally produced fish-based products were developed: an RUTF paste (NumTrey-Paste) for treatment and 2 wafer versions, one for prevention (NumTrey-RUSF) and one for treatment (NumTrey-RUTF). Objective: To assess the acceptability of NumTrey-Paste and NumTrey-RUSF in comparison to a standard biscuit product (BP-100) used for the treatment of SAM. Methods: Acceptability of NumTrey-RUSF and NumTrey-Paste was tested in a nonblinded crossover taste trial among children (n = 52), aged ≥ 6 months to 18 years, and their caregivers. Eight organoleptic qualities were assessed on a 5-point hedonic scale, as well as a ranking test. A score of 1 to 3 was categorized as acceptable. The acceptability of NumTrey-RUTF was assessed using the caregivers' perception during an SAM treatment intervention. Results: Taste trial: The proportion of children categorizing products as overall acceptable was lowest for NumTrey-Paste compared to for BP-100 and NumTrey-RUSF (21% vs 43% [BP-100] and 36% [NumTrey-RUSF]). No difference was found in the proportion of children who ranked BP-100 or NumTrey-RUSF as "liked most" ( P > .05). Acceptability of NumTrey-RUSF ranked highest in appearance and taste (caregiver), whereas acceptability of NumTrey-Paste was ranked lowest in appearance and smell among the products. Intervention trial: The acceptability of NumTrey-RUTF increased from 72% to 86%. Conclusions: The overall acceptability was ranked lowest for a pure paste product. However, filling the paste into a wafer made the product more acceptable.